Fused deposition modeling: process, materials, parameters, properties, and applications - Kumaresan, Rajan; Mahendran, Samykano; Kumaran, Kadirgama; Wan Sharuzi, Wan Harun; Rahman, Md. Mustafizur (Springer, 2022)
In recent years, 3D printing technology has played an essential role in fabricating customized products at a low cost and faster in numerous industrial sectors. Fused deposition modeling (FDM) is one of the most efficient and economical 3D printing techniques. Various materials have been developed and studied, and their properties, such as mechanical, thermal, and electrical, have been reported. Numerous attempts to improve FDM products’ properties for applications in various sectors have also been reported. Still, their applications are limited due to the materials’ availability and properties compared to traditional fabrication methods. In 3D printing, the process parameters are crucial factors for improving the product's properties and reducing the machining time and cost. Researchers have recently investigated many approaches for expanding the range of materials and optimizing the FDM process parameters to extend the FDM process’s possibility into various industrial sectors. This paper reviews and explains various techniques used in 3D printing and the various polymers and polymer composites used in the FDM process. The list of mechanical investigations carried out for different materials, process parameters, properties, and the FDM process's potential application was discussed. This review is expected to indicate the materials and their optimized parameters to achieve enhanced properties and applications. Also, the article is highly anticipated to provide the research gaps to sustenance future research in the area of FDM technologies.